Humoral and Cellular Immune Responses to SARS–CoV‐2 Infection and Vaccination in Autoimmune Disease Patients With B Cell Depletion. Issue 1 (23rd November 2021) - Simon, David; Tascilar, Koray; Schmidt, Katja; Manger, Bernhard; Weckwerth, Leonie; Sokolova, Maria; Bucci, Laura; Fagni, Filippo; Manger, Karin; Schuch, Florian; Ronneberger, Monika; Hueber, Axel; et al.
Abstract : Objective: B cell depletion is an established therapeutic principle in a wide range of autoimmune diseases. However, B cells are also critical for inducing protective immunity after infection and vaccination. We undertook this study to assess humoral and cellular immune responses after infection with or vaccination against SARS–CoV‐2 in patients with B cell depletion and controls who are B cell–competent. Methods: Antibody responses (tested using enzyme‐linked immunosorbent assay) and T cell responses (tested using interferon‐γ enzyme‐linked immunospot assay) against the SARS–CoV‐2 spike S1 and nucleocapsid proteins were assessed in a limited number of previously infected (n = 6) and vaccinated (n = 8) autoimmune disease patients with B cell depletion, as well as previously infected (n = 30) and vaccinated (n = 30) healthy controls. Results: As expected, B cell and T cell responses to the nucleocapsid protein were observed only after infection, while respective responses to SARS–CoV‐2 spike S1 were found after both infection and vaccination. A SARS–CoV‐2 antibody response was observed in all vaccinated controls (30 of 30 [100%]) but in none of the vaccinated patients with B cell depletion (0 of 8). In contrast, after SARS–CoV‐2 infection, both the patients with B cell depletion (spike S1, 5 of 6 [83%]; nucleocapsid, 3 of 6 [50%]) and healthy controls (spike S1, 28 of 30 [93%]; nucleocapsid, 28 of 30 [93%]) developed antibodies. T cell responses against the spike S1 and nucleocapsid proteins were found in both infected and vaccinated patients with B cell depletion and in the controls. Conclusion: These data show that B cell depletion completely blocks humoral but not T cell SARS–CoV‐2 vaccination response. Furthermore, limited humoral immune responses are found after SARS–CoV‐2 infection in patients with B cell depletion.